Implementasi Program Literasi Al-Qur’an dan Rohis Dalam Upaya Peningkatan Karakter Relegius Pada Siswa MTs. Assa’adah Bogor - Nurul Zibad (Jurnal Riset Multidisiplin Edukasi, 2025)
Education plays a fundamental role in shaping high-quality and morally upright generations, not only intellectually intelligent but also possessing strong and noble character. In Indonesia, as a country with a Muslim majority population, Islamic religious education holds a significant and crucial role, especially at the Madrasah Tsanawiyah (MTs) level. MTs, as a junior high school level with an Islamic distinctive characteristic, bears a great responsibility in holistically developing students' potential, including the aspect of religious character. The study uses a qualitative method with a descriptive case study research approach. It systematically, accurately, and in writing analyzes phenomena, symptoms, and facts related to the implementation of Al-Qur’an literacy and Rohis in an effort to enhance the religious character of students at MTs. Assa’adah. This program helps students to improve their spiritual awareness, noble character, and understanding of the importance of Islamic values. Factors influencing the program's success are the school's commitment, good cooperation, communication, and support from parents, as well as active student participation. The results of this study show that this program can be an effective asset for improving the religious character of students at MTs. Assa’adah Bogor.